Effect of rice straw fiber and Polyethylene glycol on polylactic acid/polyhydroxybutyrate-valerate blends - Nurul Hani Md Zubir (School of Bioprocess Engineering, 2016)
In this study, biopolymers that have been considered are PLA and PHBV. In the first series, the study focused on the blends of PLA with PHBV while the second series focused on the addition of natural filler into the blends by varying the RS powder content between 5% and 25%. The third series represented the effect of PEG on 50% PLA 50% PHBV with 5% to 25% of RS fiber content. The mixing process was carried out using heated two-roll mill (DW5110). The blends were then subjected to mechanical, morphological, thermal and physical test. For biodegradation test, the blends were investigated through natural weathering and soil burial test.